Programming Microsoft ASP.NET 4 - Esposito, Dino, 1965- (Microsoft Press, 2011)
Provides information on building Web applications using ASP.NET 4, covering such topics as managing and validating user input, choosing server controls, using patterns for data access, and implementing security features.